An analytical approach to the effects of zakat on poverty rates in Algeria - djefafla, abdelaali; boukra, kamilia (Journal of Research in Finance and Accounting, 2022)
This study aimed to highlight the impact of zakat proceeds in Algeria on poverty in the country during the period 2003/2021. The study concluded, according to the condition of 1.25, that the impact of the proceeds of the Zakat Fund on poverty levels in Algeria is relatively weak due to the lack of its outcome and its focus on a wide category of society, but it remains impossible to measure the impact of Zakat money due to the absence of a compulsory zakat system because Algeria depends on the capital tax